Minimally Invasive Microsurgery for Cerebral Contusions - Faleiro, Rodrigo Moreira; Moraes, Vítor Vieira de Souza; Belo, João Tiago Alves; Ribeiro, Thales Francisco; Greco, Chiara Menezes; Rossi, Vitor Bernardes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Traumatic brain injury (TBI) is among the main causes of death and neurological sequelae worldwide. Injuries are classified as diffuse (diffuse axonal injury and brain swelling) or focal (cerebral contusion [CCo], epidural hematoma, and acute subdural hematoma). Among all TBIs, CCos are the most frequent focal lesion, and treatment modalities are many. Hematoma evacuation using large craniotomies has been well described in the literature. The main goal of the present study is to discuss the advantages of minimally invasive approaches for the treatment of CCos, regarding operative time, blood loss, and postoperative tomographic results.Methods An integrative literature review was conducted on the SciELO, LILACS, and PubMed databases. Seven case reports were included in the present study. Retrospective data collection was performed, analyzing gender, age, Glasgow coma scale score on hospital admission, surgical approach, and postoperative (tomographic) results.Results The minimally invasive keyhole approach was used in seven patients with CCos. The supraorbital approach (n = 5) was performed for frontal lobe contusions, and the minipterional approach (n = 2) was performed for temporal lobe contusions. All cases had adequate hematoma evacuation, confirmed by postoperative computed tomography scans.Conclusion The minimally invasive approaches were effective for hematoma evacuation, with adequate clinical and radiological postoperative results.
Keywords: brain contusion; minimally invasive surgery; brain trauma; traumatic brain injuries; microsurgery; trauma surgery